2022
DOI: 10.1113/ep090042
|View full text |Cite
|
Sign up to set email alerts
|

AGEs–RAGE axis mediates myocardial fibrosis via activation of cardiac fibroblasts induced by autophagy in heart failure

Abstract: Heart failure is the end stage of cardiovascular disease and is a critical medical condition that poses an important therapeutic challenge for physicians owing to its high morbidity and mortality. Myocardial fibrosis is part of the remodelling process that occurs in heart failure. Many studies have shown that advanced glycation end products (AGEs) and receptor for advanced glycation end products (RAGE) are implicated in fibrosis and autophagy, but the mechanism remains unclear. In this study, we elucidated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Heart‐resident macrophages are activated into pro‐inflammatory M1 type to trigger inflammatory response, resulting in accelerated deterioration of cardiac function in HF 11,12,17 . Cardiac fibroblasts are activated to trigger myocardial fibrosis in HF 18,19 . Single‐cell RNA sequencing of pressure overload‐induced pathological cardiac hypertrophy in mice showed that macrophage activation and subtype switching, a key event at middle‐stage of cardiac hypertrophy 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Heart‐resident macrophages are activated into pro‐inflammatory M1 type to trigger inflammatory response, resulting in accelerated deterioration of cardiac function in HF 11,12,17 . Cardiac fibroblasts are activated to trigger myocardial fibrosis in HF 18,19 . Single‐cell RNA sequencing of pressure overload‐induced pathological cardiac hypertrophy in mice showed that macrophage activation and subtype switching, a key event at middle‐stage of cardiac hypertrophy 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the AGE/RAGE signaling pathway in diabetic complications can trigger fibroblast activation in the heart, leading to fibroblast-mediated matrix remodeling in HF ( 41 , 42 ). The present study further emphasizes the crucial roles of the AGE/RAGE signaling pathway in diabetic complications in the pathogenesis of DCM-induced HF.…”
Section: Discussionmentioning
confidence: 99%
“…RAGE is composed of an extracellular domain, a transmembrane protein and a highly charged cytoplasmic domain consisting of 43 amino acids[ 27 ]. Elevated RAGE expression and activation of AGEs-RAGE signaling have been found in a variety of diseases[ 28 , 29 ]. Our previous studies have confirmed that RAGE accelerated the progression of diabetic calcification[ 30 ].…”
Section: Discussionmentioning
confidence: 99%